The sense of coherence scale: psychometric properties in a representative sample of the Czech adult population - Tušl, Martin; Šípová, Ivana; Máčel, Martin; Cetkovská, Kristýna; Bauer, Georg F (BMC psychology, 2024)
BACKGROUND: Sense of coherence (SOC) is a personal resource that reflects the extent to which one perceives the world as comprehensible, manageable, and meaningful. Decades of empirical research consistently show that SOC is an important protective resource for health and well-being. Despite the extensive use of the 13-item measure of SOC, there remains uncertainty regarding its factorial structure. Additionally, a valid and reliable Czech version of the scale is lacking. Therefore, the present study aims to examine the psychometric properties of the SOC-13 scale in a representative sample of Czech adults. METHODS: An online survey was completed by 498 Czech adults (18-86 years old) between November 2021 and December 2021. We used confirmatory factor analysis to examine the factorial structure of the scale. Further, we examined the variations in SOC based on age and gender, and we tested the criterion validity of the scale using the short form of the Mental Health Continuum (MHC) scale and the Generalized Anxiety Disorder (GAD) scale as mental health outcomes. RESULTS: SOC-13 showed an acceptable one- and three-factor fit only with specified residual covariance between items 2 and 3. We tested alternative short versions by systematically removing poorly performing items. The fit significantly improved for all shorter versions with SOC-9 having the best psychometric properties with a clear one-factorialstructure. We found that SOC increases with age and males score higher than females. SOC showed a moderately strong positive correlation with MHC, and a moderately strong negative correlation with GAD. These findings were similar for all tested versions supporting the criterion validity of the SOC scale. CONCLUSION: Our findings suggest that shortened versions of the SOC-13 scale have better psychometric properties than the original 13-item version in the Czech adult population. Particularly, SOC-9 emerges as a viable alternative, showing comparable reliability and validity as the 13-item version and a clear one-factorial structure in our sample.
Keywords: Psychometrics; Young Adult; Male; mladý dospělý; Adolescent; Česká republika; Adult; Aged; dospělí; mužské pohlaví; senioři; Confirmatory factor analysis; reprodukovatelnost výsledků; průzkumy a dotazníky; Salutogenesis; faktorová analýza statistická; Reproducibility of Results; mladiství; Czech Republic; Factor Analysis, Statistical; životní smysluplnost; senioři nad 80 let; lidé; ženské pohlaví; psychometrie; Humans; Mental health; Sense of coherence; Aged, 80 and over; Czech adult population; Sense of Coherence; Female; Surveys and Questionnaires; lidé středního věku; Middle Aged